2000
DOI: 10.1046/j.1365-2567.2000.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

γδ T‐cell anergy in human immunodeficiency virus‐infected persons with opportunistic infections and recovery after highly active antiretroviral therapy

Abstract: Summary γδ T lymphocytes recognize non‐peptidic microbial antigens without antigen processing and major histocompatibility complex (MHC) restriction, representing an early defence mechanism against invading pathogens. As a defective response to non‐peptidic antigens was observed in human immunodeficiency virus‐positive (HIV+) persons, the aims of this study were twofold: to analyse the incidence of γδ T‐cell anergy in HIV+ patients with opportunistic infections/co‐infections (HIV‐OIC), and to investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 25 publications
6
48
2
Order By: Relevance
“…These relatively high reactivities of human V␥9V␦2 T cells to NpAgs may be induced by environmental stimuli or subclinical infections (17). Healthy human low responders are rare and are particularly found among newborns (29), elderly persons (30), and immunocompromised hosts (22,31,32). It is conceivable that a regular "environmental boosting" with NpAgs may be required to maintain the natural immune activity mediated by ␥␦ T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These relatively high reactivities of human V␥9V␦2 T cells to NpAgs may be induced by environmental stimuli or subclinical infections (17). Healthy human low responders are rare and are particularly found among newborns (29), elderly persons (30), and immunocompromised hosts (22,31,32). It is conceivable that a regular "environmental boosting" with NpAgs may be required to maintain the natural immune activity mediated by ␥␦ T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of V␥9V␦2 ϩ T cells after 10 days of culture was determined by cytometric analysis using double staining with anti-CD3 and anti-TCR-V␦2 mAbs coupled to PE or FITC, respectively. V␦2 expansion index was calculated dividing the absolute number of V␦2 ϩ T cells in stimulated cultures by the absolute number of V␦2 ϩ T cells in unstimulated cultures (20,21). The IPP-driven PBMC proliferation assay was performed in triplicate in 96-well flat-bottom plates with 2.5 ϫ 10 5 PBMC/ml in 0.2 ml containing 5 U/ml rIL-2 with or without 100 M IPP.…”
Section: Cell Preparation and Stimulationmentioning
confidence: 99%
“…It has clearly been shown that T cell anergy is present in HIV-infected patients with opportunistic infections (31) and that HIV infection-induced defective IL-2 production in T cells can be partially restored by highly active antiretroviral therapy (32). Other studies showed that anergy in T cells can be induced by HIV-1 proteins gp120 (33) and Env (34) and can be reversed by IL-2 (35,36).…”
Section: Discussionmentioning
confidence: 99%